Mechatronics design of an unmanned hovercraft system / Wahyudi Martono and Muneeb Yousuf - Martono, Wahyudi; Yousuf, Muneeb (2008)
Recently, an efficient transportation system is required due to the reducing energy sources. One of the alternative solutions is the use of hovercraft for transportation system. The hovercraft is an efficient system since it is almost a frictionless system. In addition it also can hover on a variety of terrains such as on land, river and sea. However the frictionless condition of the hovercraft causes the difficulty of controlling its trajectory motion. To overcome this problem, this paper describes the mechatronics design approach in the design and development of an automatic hovercraft system. The mechatronics design approach is primarily based on the synergistic integration of mechanical and electronic elements coordinated by control architecture. A prototype of a hovercraft is design and developed. Moreover, for controlling the motion of the hovercraft, an automatic control system is designed and developed. The automatic hovercraft is tested experimentally to follow a certain trajectory. The experimental result shows that the motion of the hovercraft successfully follows the desired path motion.